2017
DOI: 10.1002/app.45565
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable baked foam made with chayotextle starch mixed with plantain flour and wood fiber

Abstract: New renewable materials are needed to reduce petroleum-based plastic packaging. The effect of plantain flour (PF) and wood fiber (WF) on the properties of starch-based foams (SBFs) were investigated. The SBFs were characterized using physical, thermal, and mechanical methods to better understand the relationship between PF and WF concentration. Contact angle values showed that the addition of WF or PF increased the hydrophobic character of the SBFs. Also, the addition of PF increased the heat transfer resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…This effect was evidenced by the decrease in CA values, showing values of 10.85 (º), 97.38 (º) and 84.77 (º) at concentrations of 10, 7.5 and 5 g of SF respectively, only with mesh number 30, but similar behavior was showed by mesh number 45 and 70 ( Table 2 ). The increase of the wood fiber content in the baked foams increases the crystalline portion of the foams, which in turn increased their hydrophobicity causing greater resistance to water permeability ( Vargas-Torres et al., 2017 ). In the present study, a similar phenomenon was observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This effect was evidenced by the decrease in CA values, showing values of 10.85 (º), 97.38 (º) and 84.77 (º) at concentrations of 10, 7.5 and 5 g of SF respectively, only with mesh number 30, but similar behavior was showed by mesh number 45 and 70 ( Table 2 ). The increase of the wood fiber content in the baked foams increases the crystalline portion of the foams, which in turn increased their hydrophobicity causing greater resistance to water permeability ( Vargas-Torres et al., 2017 ). In the present study, a similar phenomenon was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in TC as the concentration of SF was increased indicates that SF provides higher resistance to heat transmission. Other studies report that the rate of heat transfer also depends on a better distribution of the fibers and the size of the cell in the matrix of the cooked foam materials ( Vargas-Torres et al., 2017 ). In the present study, the statistical analysis (α = 0.05) showed that the concentration of SF influenced the rate of heat transfer through the different BBF samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tests concerning the solubility of the forms were performed in triplicate following the methodology proposed by Torres et al [21]. More specifically, 3 × 3 cm samples were cut and stored for seven days in a desiccator with silica, with an ambient temperature of approximately 24 • C. The samples were then weighed and placed in glass beakers containing 80 mL of distilled water.…”
Section: Solubilitymentioning
confidence: 99%